THE USE OF HYDROLATE FIREWEED IN THE PRODUCTION OF ORGANIC SOAP - Ekaterina Nikolaevna Kholodova; Anastasia Artemova Koverchenko (Современная наука и инновации, 2022)
Promising natural ingredients in the production of organic Soaps include herbs, oils, powders from vegetable raw materials. Received hydrolat willow-herb and the possibility of its use in the production of natural Soaps.